Utilizing Industry 4.0 to Overcome the Main Challenges Facing UAE to Achieve the (SDG6.b) Goal of the United Nation Sustainable Development - Alnaqbi, Amel; Al Hazza, Muataz (International Journal of Energy Economics and Policy, 2023)
United Arab Emirates (UAE) is described as a desert country facing significant challenges in managing water resources due to its arid climate and rapid population growth. In recent years, UAE government has prioritized sustainable water management practices. It has made progress towards achieving the Sustainable Development Goal (SDG) 6.b, which aims to "support and strengthen the participation of local communities in improving Water and sanitation management. The main purpose of this research is to investigate the UAE’s significant challenges in achieving SDG6.b Goal of the United Nations Sustainable Development Goals for 2030. Concurrently, this research concentrates on overcoming these challenges. As one of the best qualitative methods, Delphi method was used to explore these challenges and how to integrate Industry 4.0 to overcome those challenges. Five experts from various areas linked to and supporting the water field were invited and accepted to be involved in this research. This research involved a comprehensive approach to prioritize the selected challenges, with the aim of achieving high consistency. The implementation of AHP and Delphi Methods incorporating two rounds of evaluation and expert feedback to reach an 80% consistency threshold. The first round was about identifying and evaluating a set of challenges using AHP method, which compares challenges based on their importance. While the second round was implemented to clarify the prioritization of challenges, this iterative process allowed adjustments based on expert insights, which increased consistency in the prioritization results. Achieving 80% consistency by making two rounds of implementation was an important milestone in this research. It ensured that the prioritization results were reliable and consistent.